EDUKASI GASTROENTERITIS AKUT DAN SINDROM DISPEPSIA DENGAN PENDEKATAN KEDOKTERAN KELUARGA - Tjahjadi, Joey Joshua V Tjahjadi; Zahrotusyifa, Aila; Ersya , M Naufal; Arya , M. Fauzan; Davega, Mutia; Ghaniyya , Nabiila; Khairani, Rita (Jurnal Pengabdian Masyarakat Trimedika, 2024)
Acute gastroenteritis is an inflammation of the stomach and intestines that causes symptoms such as diarrhea, nausea and vomiting lasting less than 14 days. Dyspepsia syndrome is a collection of symptoms commonly found in the community, characterized by a sensation of pain or discomfort in the upper area of the solar plexus. The aim of this activity is to determine the description and causes of acute gastroenteritis and dyspepsia syndrome using the principles of a family medicine approach based on evidence based medicine in patients by identifying risk factors, clinical problems, and patient management using a patient centered approach and family approach. Methods are obtained through history taking and physical examination. Home visits were done to obtain a complete data and to do an analysis on the family’s medicine, psycho-social and environmental surroundings. Those Analysis includes holistic family medicine diagnosis and family function management plan. The results showed that a 59-year-old woman suffering from acute gastroenteritis and dyspeptic syndrome who has internal risk factors such as age approaching old age category, irregular eating patterns with unhygienic eating habits, education has been carried out for patients and their families about disease, drugs, lifestyle, and proper diet. The conclusion is a process of changing the patient's behavior to control food hygiene and maintain regular meal times, always wash hands especially before eating to prevent recurrence of the disease. The role and attention of the family is very important in the care and management of sick family members.